Chemoenzymatic synthesis and biological evaluation of enantiomerically enriched 1-(β-hydroxypropyl)imidazolium- and triazolium-based ionic liquids - Borowiecki, Paweł; Milner-Krawczyk, Małgorzata; Plenkiewicz, Jan (Beilstein Journal of Organic Chemistry, 2013)
Racemic 1-(β-hydroxypropyl)azoles were prepared by solvent-free direct regioselective ring opening of 1,2-propylene oxide with imidazole or 1,2,4-triazole. Lipase-catalyzed transesterification of alcohols with vinyl acetate resulted in kinetic enantiomers resolution. Separated (S)-enantiomers of (+)-1-(1H-imidazol-1-yl)propan-2-ol and (+)-1-(1H-1,2,4-triazol-1-yl)propan-2-ol were quaternized with alkyl bromides or iodides, yielding novel optically active ionic liquids. Racemic salts were tested against a wide range of microorganisms.
Keywords: antibiotics; antifungal agents; double derivatization; enzyme catalysis; ionic liquids